2021
DOI: 10.1002/cnr2.1419
|View full text |Cite
|
Sign up to set email alerts
|

First line immunotherapy extends brain metastasis free survival, improves overall survival, and reduces the incidence of brain metastasis in patients with advanced melanoma

Abstract: Background: Recent advances in targeted therapy and immunotherapy have improved the prognosis of melanoma patients but brain metastasis remains a major challenge. Currently, it is unclear how existing therapies can be best used to prevent or treat brain metastasis in melanoma patients. Aims:We aimed to assess brain metastasis free survival (BMFS), overall survival (OS), incidence of brain metastases, and sequencing strategies of immunotherapy and targeted therapy in patients with BRAF-mutated advanced melanoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…A retrospective study by Wang et al assessed BMFS in a cohort of BRAF mut , but not BRAF wt patients, receiving ICI or BRAF+MEK TT. 21 This work showed a prolonged BMFS for patients who received ICI as 1L-therapy compared with patients who received BRAF+MEK. These findings were based on propensity scored matching of single variables and not on a multivariate Cox regression analysis including all important prognostic variables as in our analysis.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…A retrospective study by Wang et al assessed BMFS in a cohort of BRAF mut , but not BRAF wt patients, receiving ICI or BRAF+MEK TT. 21 This work showed a prolonged BMFS for patients who received ICI as 1L-therapy compared with patients who received BRAF+MEK. These findings were based on propensity scored matching of single variables and not on a multivariate Cox regression analysis including all important prognostic variables as in our analysis.…”
Section: Discussionmentioning
confidence: 74%
“…19 A French group analyzed 293 melanoma patients without brain metastases who were treated with either anti-PD-1 or anti-PD-L1 antibodies or other systemic therapies (including BRAF inhibitors and chemotherapy) and found a lower incidence of MBM in the PD-1 group compared with patients treated with other therapies. 20 The results of this study are weakened by the fact, that BRAFmut patients were not assessed separately in the multivariate analysis 21 This work showed a prolonged BMFS for patients who received ICI as 1L-therapy compared with patients who received BRAF+MEK. These findings were based on propensity scored matching of single variables and not on a multivariate Cox regression analysis including all important prognostic variables as in our analysis.…”
Section: Discussionmentioning
confidence: 78%
“…In a retrospective cohort of 683 BRAF V600 mutated patients, treated over an 8-year period (2011-2019), it was found that the incidence of brain metastasis was approximately double with initial targeted therapy versus immunotherapy (31 versus 16%) and median brain metastases-free survival was 11 months with targeted therapy compared with 42 months with immunotherapy. Therefore, this study suggests that immunotherapy is more effective than targeted therapy in preventing or delaying the occurrence of brain metastases from melanoma, in both adjuvant and metastatic contexts 69 .…”
Section: Discussionmentioning
confidence: 89%
“…Second-line double immunotherapy might be a preferable option with the hazard of fast and dangerous CNS metastases progression following sudden TT discontinuation, a risk that might be overcome by local treatment of the most threatening lesions. Conversely, the interest of second-line triplet TT/antiPD1 therapy in case of morphological or clinical primary or secondary CNS progression after first-line double immunotherapy remains to be investigated [36].…”
Section: Discussionmentioning
confidence: 99%